Dissociative disorders: A study of clinico-demographic profile and associated stressors - Thapa, R (Journal of Psychiatrists’ Association of Nepal, 2015)
Objectives: To study relevant clinico-demographic profile and stressors of dissociative disorders. Methods: this is a case control study of 39 cases of dissociative disorders and compared with 39 controls using a self designed questionnaire and G. Singh’s Presumptive Stressful Life Events Scale (PSLE). Results: The mean age of the cases was 21.23 years. Cases of Dissociative motor disorders had significantly higher age (26.4 yrs) as compared to dissociative convulsion (18.8 yrs) and dissociative stupor (20.6 yrs). (38.5%).Two thirds of the cases had comorbid neuro-psychiatric illness, the commonest one being depression (35.9%). The cases had more stressful life events in the past one year as well as whole life when compared to controls. Family conflict was seen to be the commonest precipitating stress. Conclusions: Dissociative disorder mainly affects young people. Dissociative motor disorder is a distinct subtype with a higher age of onset. Presence of neuro-psychiatric co-morbidity is the rule rather than exception. Psychosocial stressors play an important role in disease production. J Psychiatric Association of Nepal Vol .3, No.2, 2014, pp: 25-30 DOI: http://dx.doi.org/10.3126/jpan.v3i2.12386